(untitled) (Applied Biological Research, 2019)
Microgreens are immature greens of edible vegetables and herbs which may serve as a good nutrient source. The present study was conducted on ten locally available plants, tested as microgreens. The study included evaluation of seed germination and growth pattern for two weeks period and nutritional characterization of selected microgreens. Results showed that the seeds of selected plants had > 80% germination and attained 6-7 cm height within two weeks. Vitamin C was high in all the microgreens tested; while thiamine, riboflavin and niacin were high in microgreens of Amaranthus viridis, Vigna radiata and Allium cepa, respectively. However, vitamin content was higher in sprouts than microgreens and mature edible parts of selected plants even though some exceptions were found. Anti-nutrients analyzed in microgreens were below the toxic levels. Microgreens had low carbohydrates and anti nutrient contents; but high vitamin contents, so these can be recommended as dietary supplement, especially for those who preferred less carbohydrate containing food supplements.